2015
DOI: 10.1371/journal.pone.0144438
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension and Chronic Kidney Disease in Chinese Population: Four-Year Follow-Up Study

Abstract: Hypertension is a well established cause of chronic kidney disease (CKD). However, the effect of prehypertension on risk of CKD is controversial. The aim of this study is to determine whether prehypertension increases the risk of CKD events in the Chinese population. We enrolled 20,034 with prehypertension and 12,351 with ideal blood pressure in this prospective study. CKD was defined as an estimated glomerular filtration rate (eGFR) <60 ml/min 1.73m2. The new occurrences of CKD events were collected during fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…After reading the full text of 45 articles, 10 articles were removed because they did not focus on CKD, 22 records were excluded because they contained no information about prehypertension, 3 were removed because they did not compare prehypertension with normal blood pressure, and the other 3 articles were excluded because they did not report 95% CI values ( S1 Table ). Finally, 7 studies were included in our meta-analysis [ 6 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the full text of 45 articles, 10 articles were removed because they did not focus on CKD, 22 records were excluded because they contained no information about prehypertension, 3 were removed because they did not compare prehypertension with normal blood pressure, and the other 3 articles were excluded because they did not report 95% CI values ( S1 Table ). Finally, 7 studies were included in our meta-analysis [ 6 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prehypertension, which was first described in the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7) [ 5 ], has attracted increased attention from nephrologists. The relationship between prehypertension and the risk of CKD is controversial, with conflicting results derived from different cohort studies [ 6 12 ]. The Ohasama Study from Japan demonstrated a significant association between prehypertension and the development of CKD in a general population.…”
Section: Introductionmentioning
confidence: 99%
“…The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC-7) proposed high BP category, including 120–139 mm Hg systolic BP (SBP) or 80–89 mm Hg diastolic BP (DBP), designated as prehypertension [7]. According to JNC-7, individuals with prehypertension have a higher risk of developing hypertension compared with those with ideal BP levels; also, they have an increased risk of cardiovascular morbidity and mortality [59]. Previous studies have shown that prehypertension is related to a 1.7-fold increase in coronary artery disease and a 3.5-fold increase in myocardial infarction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a clustering of cardiovascular disease risk factors was also observed in the prehypertension population of Han and Mongolian adults [ 10 ]. A four-year follow-up study indicated that prehypertension significantly increased the occurrence of chronic kidney disease in Chinese adults [ 11 ]. Meta-analyses have demonstrated that prehypertension, as well as hypertension and diabetes, are significantly associated with the risk of cardiovascular events including coronary heart disease, stable angina and stroke.…”
Section: Introductionmentioning
confidence: 99%